The Next Generation of ABA Providers - Dixon, Mark R. (Behav Anal Pract, 2014)
The imbalance of supply and demand for behavior analytic services will change in the near future. Behavior analysts, who want to survive in an increasing competitive marketplace, will need to show quality results and better results than the next behavior analyst. Trumpet Behavioral Health is a company designed to infuse scientific research with clinical practices. In the years ahead, look to companies like Trumpet as role models of the next generation of autism service providers.